Modeling Fluid Dynamics in the Ocean and Atmosphere - Prants, S.V. (Discontinuity, Nonlinearity, and Complexity, 2026)
This Special Issue collects together works on analytic solutions and numerical simulation of fluid dynamics in the ocean and atmosphere. The contributed papers address a variety of problems in geophysical fluid dynamics including formation of coherent structures in random hydrodynamic flows, hyperbolicity in the ocean, mesoscale surface and deep vortices in the ocean, formation of vocalized atmospheric vortices and motion of tropical cyclones, convective instability and nonlinear structures in systems with a multi-component convection, instability development in shear stratified flows and others.